A neglected case of chronic abdominal pain due to Lapsi seeds: A unique foreign body at unusual location. (2020) - Kadel, Dhruba; Bhuju, Shashinda; Thapa, Bikash Raj; Sah, Sandeep Kumar
Highlights: Chronic partial jejunal obstruction leading to various non specific abdominal symptoms since 40 years. The first reported case of Lapsi seed stones causing partial jejunal obstruction. No change in morphological features of Lapsi seed stones when resided for long within human Gastrointestinal tract. First demonstration of radiological features of Lapsi seed stones both in vivo as well as in vitro. When patient not evaluated by non-physician and non-surgeon could delay diagnosis and improper treatment. Abstract: Introduction: Foreign body ingestion is less common in healthy adult population. Obstructive symptom caused by foreign body at unusual site of gastrointestinal (GI) tract is even rarer. Presentation of case: A 60-year-old female presented to the surgery outpatient department (SOPD) with 40-years of non-specific abdominal pain. Over the years, at various health facilities, multiple abdominal and pelvic ultrasounds were performed. No etiology was identified. A contrast enhanced computed tomography (CECT) of the abdomen found a short segment stricture in distal jejunum and dilated proximal jejunum with multiple hyper dense foreign bodies within the distal part of dilated jejunum. An exploratory laparotomy revealed multiple seed stones of Nepali Hog Plum (Scientific name: Choerospondias axillaris ; Nepali Language: Lapsi) resided freely within the dilated and inflamed distal jejunum along with two marked strictures and a narrowed lumen at 7 cm apart at the terminal part of unhealthy jejunum. The seeds were successfully removed and a jejunoileal bypass was performed. The patient had an uneventful postoperative recovery. Discussion: Lapsi seeds could reside in human gastrointestinal tract for prolonged period and are indigestible in human digestive system that could lead to various inflammatory changes in gastrointestinal tracts causing obstructive symptoms. Widely consumed fruits in Nepal, lapsi seeds when swallowed even by healthy individuals, could effect in gastrointestinal tract. Conclusion: Lapsi seeds could act as foreign body and obstruct human gastrointestinal tract. Healthcare professionals must approach mystery cases with diligence and thoroughness and timely referral to well equipped center could prevent significant morbidity.